2014
DOI: 10.1104/pp.114.237180
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis Glutathione Transferases U24 and U25 Exhibit a Range of Detoxification Activities with the Environmental Pollutant and Explosive, 2,4,6-Trinitrotoluene      

Abstract: The explosive 2,4,6-trinitrotoluene (TNT) is a major worldwide military pollutant. The presence of this toxic and highly persistent pollutant, particularly at military sites and former manufacturing facilities, presents various health and environmental concerns. Due to the chemically resistant structure of TNT, it has proven to be highly recalcitrant to biodegradation in the environment. Here, we demonstrate the importance of two glutathione transferases (GSTs), GST-U24 and GST-U25, from Arabidopsis (Arabidops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
84
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(88 citation statements)
references
References 52 publications
4
84
0
Order By: Relevance
“…One of the three processes reported was the direct conjugation of TNT through nucleophilic substitution of the nitro group to form 2-glutathionyl-4,6-dinitrotoluene. The other two products were C-glutathionylated HADNT isomers at the methyl group of TNT [42] (Fig. 1).…”
Section: Metabolism Of Tntmentioning
confidence: 95%
See 1 more Smart Citation
“…One of the three processes reported was the direct conjugation of TNT through nucleophilic substitution of the nitro group to form 2-glutathionyl-4,6-dinitrotoluene. The other two products were C-glutathionylated HADNT isomers at the methyl group of TNT [42] (Fig. 1).…”
Section: Metabolism Of Tntmentioning
confidence: 95%
“…Collectively, the results do not indicate the involvement of glutathione conjugates. However, glutathione conjugates were identified in a recent study investigating the GSTs, GSTU24, and GSTU25 [42]. These GSTs were chosen for their high activity to TNT and were studied in transgenic Arabidopsis.…”
Section: Metabolism Of Tntmentioning
confidence: 99%
“…4 Previously, GSTs had been shown to be upregulated in response to TNT Keywords: Arabidopsis thaliana, environmental pollutant, Glutathione transferases, TNT, xenobiotic detoxification, 2, 4, 6-trinitrotoluene treatment, and their involvement in TNT detoxification hypothesized. [8][9][10][11][12] Our study 13 investigated GST-U24 and GST-U25, the 2 Arabidopsis GSTs most highly upregulated in response to TNT under our treatment conditions. We demonstrated that Arabidopsis plants overexpressing GST-U24 or GST-U25 removed more TNT from soil and were more resistant to TNT toxicity than wild type plants, due to the direct glutathionylation of TNT.…”
mentioning
confidence: 99%
“…GST-U24 produced predominantly conjugate 1 (C-glutathionylated 4-HADNT), whereas GST-U25 produced conjugates 1, 2 (C-glutathionylated 2-HADNT) and 3 (2-glutathionyl-4,6-dinitrotoluene). 13 Conjugate 3 is of particular interest due to the denitration of TNT; the nitro groups offer stability to the ring through resonance.…”
mentioning
confidence: 99%
See 1 more Smart Citation